Peran Diakonia Profetik dalam Mengatasi Eksploitasi Penenun Ulos di Kecamatan Sipoholon - Sinaga, Sarah; Siregar, Nina Febriani; Siburian, Sri Rezeki (JURNAL DIAKONIA, 2025)
The problems experienced by ulos weavers are currently quite concerning. The inequality of the Ulos weavers in Sipoholon Subdistrict, North Tapanuli Regency, face inequality in selling prices that are not proportional to the results and work time. Exploitation by agents who offer low prices is further exacerbated by limited market access and reduced buyers due to the COVID-19 pandemic, which has a negative impact on the fulfillment of daily needs. This research discusses the impact of price inequality and exploitation on the lives of weavers and the role of the church in overcoming it. Using qualitative methods through literature studies by collecting library data, reading and recording and processing data objectively, systematically, analyzing and critically about ulos cloth weavers in North Tapanuli, especially the Sipoholon sub-district. he results show that Christian theology itself states that justice is important. The church needs to play an active role to fulfill its vocation to give “good news” to the oppressed weavers by helping to release them from the shackles of exploitation through a prophetic diaconal approach that focuses on liberation theology.